The Humanistic Paradigm in Deep Learning: A Philosophical Analysis of Teachers' Roles in Fostering Meaningful Understanding - Retna Hani Dafiska; Hanipah Khoeriyah; Jenuri Jenuri (Journal of Innovation and Research in Primary Education, 2026)
Deep learning implementation in elementary schools requires philosophical grounding to foster meaningful understanding. This study analyzes deep learning through the humanistic paradigm lens, focusing on teachers' roles in cultivating students' meaningful understanding within the Independent Curriculum context. A descriptive qualitative design was employed involving three fourth-grade teachers from a public elementary school. Data were collected through semi-structured interviews, non-participatory classroom observations over six weeks, and document analysis. Data analysis followed Miles et al.'s interactive model with triangulation, member checking, and peer debriefing ensuring trustworthiness. Findings reveal that teachers function as facilitators creating psychologically supportive environments through contextual questioning, collaborative inquiry, and reflective practices. Students demonstrated multidimensional engagement (behavioral, emotional, and cognitive) constructing understanding through personalized language and peer interaction. Teacher-student relationships exhibited empathy, unconditional positive regard, and authenticity. An unexpected finding showed discrepancies between students' written assessment performance and oral conceptual demonstration, suggesting conventional assessments inadequately capture meaningful learning. Results validate humanistic learning theory, demonstrating that affective and relational dimensions are integral to conceptual understanding. The synergistic relationship between emotional safety and cognitive engagement challenges purely cognitive learning models. Findings necessitate reconceptualizing teacher professional development to address empathic presence and assessment systems to honor multiple demonstration modalities, addressing critical equity concerns for diverse learners.